PENGARUH TINGKAT PENDIDIKAN, PELATIHAN DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI POLTEKKES KEMENTERIAN KESEHATAN PALU - Asriwidyayanti, Asriwidyayanti (Katalogis, 2018)
The study identifies the influence of education level, training and work discipline on the performance of officials in health polytechnic the ministry of health Palu. The aim is to determine and analyze simultaneous and partial influence of education level, training and work discipline on the performance of officials in health polytechnic the ministry of health Palu. Method of analysis is multiple linear regressions with 78 respondents. The result finds that the correlation berween independent variables of educational level, training and work discipline and the performance of officials in health polytechnic, the ministry of health, Palu is 0.795, which shows a strong correlation berween independent and dependent variables. The value of adjusted R square or determinant coefficient,which is meant to determine the influence of education level, training and work discipline on the performance of officials in health polytechnic the ministry of health Palu is 0.617 or 61.7%. This reflects that the influence of independent variables on the dependent variables is 61.7% while the remaining of 38.3% influenced by other variables that are not included in this study. The study show that independent variables simultaneously and partially influence performance of officials in health polytechnic. The ministry of health Palu due to the level of significance that is lower than Î± = 0.05. therefore, the four hypotheses are accepted.